The Importance of Knowing The Emotions and Personality of The Patient In Completing The Odontal Therapeutic Act - Oprea Valentin BUȘU; Elena Cristina ANDREI (Social Sciences and Education Research Review, 2018)
The present study proposes an analysis of the importance of knowing the emotions, in the context of fact if, a few years ago, dentistry focused strictly on the treatment of somatic symptoms, without giving importance to the psychic and emotional aspects of the patient, the dentists recently sought to improve themselves in the field of patient psychology and state prior to his presentation to the cabinet, as well as post-procedure. Within the present context we wanted to reflect that the majority of the population has a certain fear of visiting the dentist, some people even developing a phobia, which will have harmful effects not only on the oral cavity but also throughout the body. The success of the odontal therapeutic act is largely conditioned by the physician's ability to empathize with the patient, to know his lifestyle and how he manages his emotions, but also to determine the type of personality he / she falls into. The physician should also take into account the patient's bio-psycho-social factors in order to be able to issue a correct diagnosis. At present, a correlation between oral cavities and psychological/social ones can easily be observed. For example, psychological stress is in most cases the causal factor of gingival inflammation. Another example can be the social factor